Health conditions and admission hospital risk in elderly women practicing waters aerobics - Casal Bortoluzz, Emanuelly; Barros, Temístocles Vicente; Brand, Caroline; Fagundes Soares, Patrícia; Roth, Maria Amélia (O Mundo da Saúde, 2016)
The aging brings a new reality to the health system, since they are more prone to chronic diseases, which demand a high cost. This study aimed to analyze the prevalence of dyspnea and fatigue and its correlation with anthropometric measurements, and hospitalization risks in elderly women engaged in water aerobics. This cross-sectional, quantitative study with 94 elderly women engaged in water aerobics. Held data collection through risk assessment questionnaires hospitalization and pulmonary function and dyspnea, and anthropometric measurements. The results showed average value of BMI, WC and WHR above the ideal (28.6 / 93.6 / 0.87 respectively). The self-rated health was positive for 74.3% of the women and about 90% had no hospitalizations in the last twelve months. Still, there are significant negative correlation between the water aerobics practice time and fatigue. Therefore, we can see the positive effects of practicing gymnastics since even with altered anthropometric results, the vast majority of older reported good health, low number of visits for treatment and hospitalization. As dyspnea and fatigue, percentage around 5% reported having dyspnea and severe/very severe fatigue, which require appropriate care.